Artistic-Cultural Perspectives in Technical-Professional Training at UTFPR-Brazil - Adriana Santos Auzani; Levi Leonido Fernandes da Silva; Antonino Manuel de Almeida Pereira; Maria Gabriel morgado (Desafio Singular, 2022)
In this research we intend to study the role of art in the creative process, in engineering courses at the Federal Technological University of Paraná (UTFPR), as a factor of technological innovation. It is a qualitative research that is characterized, as a method, for adopting a naturalistic and descriptive perspective. The sample is composed of students and graduates (10); by teachers, coordinators and directors of Education and the Pato Branco Campus (10); Dean (1); Entrepreneurs (4). In the analysis and discussion of results, from semi-structured interviews, we opted for Content Analysis having in perspective the Theory of Social Representations of Moscovici (1978). Among the main conclusions, we highlight the valorization of creative, interpersonal and communicative skills, as fundamental competences in the formation of an engineer. It is also highlighted that the role of art in engineering can enhance creativity and constitute it as a factor of technological innovation. This being able to promote the imagination and the capacity for abstraction necessary and fundamental in the design of projects in engineering and in the communicational plan. The integration of art in formal training, at the moment, does not constitute an institutional option nor does it contribute to a significant dialogical relationship between curricular activities and extracurricular artistic activities ("Grupo de Teatro Artífice" of UTFPR). Keywords: Higher Education, Engineering, Art, Creativity, Communication, Culture